Rancang Bangun Sistem Manajemen Inventaris Gudang Berbasis Web pada Toko Bangunan UD Citra Perdana - Adrian Ramadhan; Farizi Ilham; Muhamad Aziz Mufashshal; Muhammad Nur Fahrurroji Assyidiq (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
UD. Citra Perdana, a building materials store, still manages its inventory manually. This often leads to recording errors, delays in identifying low stock, and slow inventory processes. This study aims to design and build a web-based Warehouse Inventory Management Information System capable of tracking incoming and outgoing stock, scanning and generating QR Code to speed up inventory processes, automatically grouping items by category, and providing a multi-role authorization mechanism (Admin/Owner and Warehouse Staff). The system development method used is the Waterfall model, consisting of requirements analysis, design, implementation, testing, and maintenance. The system is built using HTML5, CSS3, Vanilla JavaScript ES6, PHP 8.x, and MySQL/MariaDB database without using any framework, and utilizes an external API for generating QR Code for items. The result of this study is an application that helps staff manage inventory data in real-time, reduces human error, and improves the store's operational efficiency. System testing shows that the camera-based QR Code Scanner works well, and the stock report export feature to Excel format accelerates the reporting process. Thus, this system is expected to be an effective solution for UD. Citra Perdana in warehouse inventory management.